Study on failure behaviors and control technology of surrounding rock in a weakly cemented soft rock roadway: A case study - Zhou, Kai; Yu, Fenghai; Tan, Yunliang; Guo, Weiyao; Zhao, Tongbin (Frontiers in Earth Science, 2023)
During coal mining, the deformation and failure of a weakly cemented soft rock roadway roof could cause difficulties for roadway support. In this paper, a combination of on-site measurement and theoretical analysis is used to solve this issue. Firstly this paper investigates the in situ deformation and failure behaviors of a soft rock roadway in a mine in Western China. Then, the failure mechanism and corresponding support principles are discussed and given. Third, various support schemes (bolt and cable reinforcement optimization, grouting, and single prop + top beam combined reinforcement) are proposed and tested. Results show the support capacity can meet the requirements after optimizing the bolt and cable reinforcement support. Due to the development of roof cracks and low grouting pressure, the grouting slurry did not completely fill the roof cracks, resulting in a poor roof control effect. The passive support of a “single prop + top beam” can effectively control the roof subsidence and achieve good application results.